Chronic Non-communicable Diseases in Health Care Workers: a Multidisciplinary Approach - Teresa Rodríguez Rodríguez; Darianna María Muñiz Cabeza (Universidad de las Ciencias Médicas de Cienfuegos, 2014)
Background: the rise of chronic non-communicable diseases requires urgent attention within the projections of the health system in order to contribute to the control and better management of the multiple risk factors that accompany them. Objective: to determine major chronic non-communicable diseases and risk factors in health care workers. Methods: a correlational, case series study including workers of the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos was conducted from January 2009 through July 2012. A two-stage sampling design was used. The sample consisted of 187 subjects. Selected variables were: sex, age, occupation, educational level, chronic diseases, behavioural risk factors and emotional risk factors. Results: women (61 %) and subjects who completed studies beyond 12th grade (48.6 %) were more commonly affected by non-communicable diseases, as well as nurses (31 %) and physicians (27.8 %) in terms of occupation. Most frequent chronic diseases were hypertension (33.69 %), diabetes mellitus (19.78 %) and ischemic heart disease (13 %). Major emotional risk factors included: stress (79.82 %), followed by anxiety (64.16 %) and depression (35.29 %). Smoking predominated in 28.87 % of the subjects. Conclusions: professionals, women and workers aged 40 to 50 years predominated. It was demonstrated that chronic conditions studied and risk factors are most common in women. Over 50 % of the workers suffer from chronic diseases. Risk factors are present in subjects both with and without chronic conditions.